Social Media Use and Early Adolescent Development: A Literature Review on Social and Academic Outcomes in Junior High School - Erna Febriany (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
The use of social media among early adolescents, particularly junior high school students, has increased significantly over the past decade. Early adolescents (ages 12–15) are in a critical phase of psychosocial development, including identity formation, social interaction, and academic adaptation. This study aims to analyze the impact of social media use on the social and academic outcomes of junior high school students based on the latest empirical evidence. The method used is a systematic literature review (SLR) of relevant research articles published between 2019 and 2025. The research process was conducted through several stages in accordance with the PRISMA guidelines, namely the identification, screening, eligibility, and inclusion stages. The findings indicate that social media has a dual impact. On one hand, social media supports the maintenance of existing friendships, provides social support, aids in identity exploration, and facilitates the sharing of academic information. On the other hand, problematic social media use is associated with an increased risk of cyberbullying, social anxiety, depression, reduced self-esteem, sleep disturbances, and academic procrastination. Protective factors such as parental support and active supervision have been shown to mitigate these negative effects. This study recommends the need for psychoeducational interventions for students and parents, as well as the integration of digital literacy into the school curriculum.